EFEKTIVITAS SENAM YOGA TERADAP PENURUNAN NYERI DISMINORE PADA MAHASISIWI DI UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI TAHUN 2020 - YULINA, RATI; INDRAWATI, INDRAWATI; NINGSIH, NENENG FITRIA (Jurnal Ners, 2020)
One of the non-pharmacological therapies in reducing dysmenorrhea pain is yoga exercises. The purpose of this study was to determine the effectiveness of yoga exercises in reducing dysminorrhea pain in students at Universitas Pahlawan Tuanku Tambusai in 2020. This type of research is a pre-experiment with a one group pretest postest design. The sample in this study was 18 students of S1 Nursing Semester IV who experienced dysmenorrhea by using purposive sampling technique. The data collection tool used was a checklist sheet. The analysis used in this study was univariate and bivariate analysis. The results showed that the average pain scale before being given yoga exercise was 5.22, the average pain scale after being given yoga exercise was 2.50, yoga exercise was effective in reducing dysminorrhea pain in students of Universitas Pahlawan 2020 with a p value of 0.000. Students who experience menstrual pain or dysmenorrhea should do yoga exercises to reduce the intensity of the pain they feel.